2021
DOI: 10.21203/rs.3.rs-212805/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal and spatial evolution patterns and prediction of drought in China in recent 500 years

Abstract: Drought is a prominent disaster in Chinese history. Analysing the spatial and temporal evolution laws of drought could provide decision supports for drought prevention and control. However, fewer studies were applied to investigate the long-term evolution rules of drought events on different spatial and temporal scales. In this paper, the spatio-temporal changes patterns of drought in China were analysed with geostatistical methods based on the 1470–2000a drought datasets in China, and then the possible future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…In recent years, the overall drought intensity in China has shown a fluctuating downward trend, and the proportion of stations with mild drought has increased year by year. Gao et al [52] have analyzed the spatiotemporal evolution characteristics of drought in China over the past 30 years based on the MCI, and they noted that drought intensity has gradually decreased in the past 30 years and that the years of strongest annual drought intensity in some of the northern river basins mainly appeared at the end of the 20th century and beginning of the 21st century. Wang et al [53], based on SPI analysis, have observed a downward trend in both the annual-scale drought station percentage and drought intensity in the Hexi Corridor region from 1960 to 2016, and also that drought intensity in the study area was mainly dominated by mild and moderate droughts.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the overall drought intensity in China has shown a fluctuating downward trend, and the proportion of stations with mild drought has increased year by year. Gao et al [52] have analyzed the spatiotemporal evolution characteristics of drought in China over the past 30 years based on the MCI, and they noted that drought intensity has gradually decreased in the past 30 years and that the years of strongest annual drought intensity in some of the northern river basins mainly appeared at the end of the 20th century and beginning of the 21st century. Wang et al [53], based on SPI analysis, have observed a downward trend in both the annual-scale drought station percentage and drought intensity in the Hexi Corridor region from 1960 to 2016, and also that drought intensity in the study area was mainly dominated by mild and moderate droughts.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, drought duration or severity may increase [5][6][7], and for drought, there are significant differences in drought recurrence periods at different time scales [8]. Since 1961, China has experienced a process from wetter to drier, with nearly 60% of meteorological stations in China showing a trend of humidification, with the areas of arid and humid regions decreasing while those of semi-arid and sub-humid regions increasing [9][10][11]. Due to the increase in precipitation and decrease in ET 0 in most parts of southern China and northwestern Xinjiang, the climate has become wetter.…”
Section: Introductionmentioning
confidence: 99%